Perception and View of Consumers on Food Irradiation and the Radura Symbol - Valenzuela-Bascunan, X; Galotto-Lopez, M; Junqueira-Conceicao Goncalve, M; Marchan-Dinten, C (2011)
The present study was aimed at carrying out a survey on the knowledge and acceptance level of food irradiation. The work was carried out in Santiago, Chile. As an above-average level country in South and Central America, the results may give an indication about the situation in other countries. The survey could also provide an indication about the impression of the public regarding the international Radura symbol, indicating on a food product that has been irradiated. A total of 497 persons were interviewed. Among the interviewed people, 76.5% did not know that irradiation could be used as a method for food preservation; 46% expressed their belief that irradiated food means the same as radioactive food. Nevertheless, 91% claimed that they would become consumers of irradiated food if they knew that irradiated is not radioactive and that proper irradiation enhances food safety; 95.8% of the interviewed persons were not familiar with the Radura symbol. However, 55.8% expressed their opinion that they would buy irradiated food because of the symbol, affirming that the Radura symbol transmits the sensation of confidence and safety. © 2010 Elsevier Ltd.